2018
DOI: 10.7759/cureus.3029
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Hematemesis in the 21st Century

Abstract: Objective: Upper gastrointestinal (GI) bleeding occurs at a rate of 40-150 episodes per 100,000 persons per year and is associated with a mortality rate of 6%-10%. We sought to determine the need for therapeutic endoscopy or surgical interventions in patients with hematemesis and the association with blood transfusion requirements.Methods: We queried the database of our large teaching facility for adult patients presenting with obvious upper GI hemorrhage (hematemesis) between 2014 and 2017. We evaluated the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
4
1
Order By: Relevance
“…In general, surgery should be considered only after all other therapeutic options have failed. It is worth mentioning that transfusion requirements did not predict the need for therapeutic interventions in our previous investigations 3,4 or the need for a second intervention to control recurrent bleeding in our present study (Table 3).…”
Section: Discussioncontrasting
confidence: 60%
See 4 more Smart Citations
“…In general, surgery should be considered only after all other therapeutic options have failed. It is worth mentioning that transfusion requirements did not predict the need for therapeutic interventions in our previous investigations 3,4 or the need for a second intervention to control recurrent bleeding in our present study (Table 3).…”
Section: Discussioncontrasting
confidence: 60%
“…Surgery or IR procedure was not required to control patients bleeding during the study period. 3,4 In light of these interesting results and data from other trials, we decided to study the natural history of GI hemorrhage in patients who have undergone therapeutic endoscopy. We found that most of our patients (91%) stabilized after therapeutic endoscopies, whereas a small group had recurrence of bleeding after the interventions (9%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations